“Open air school” – A “new” space for educational school reform and life reform in the interwar period in Czechoslovakia (Sudeten German and Czech examples) - Kasper, Tomas (Historia y Memoria de la Educación, 2020)
The study analyses two examples of so-called open air schools in Czechoslovakia in the interwar period – a Czech and a Sudeten German example of “new education”. The article presents selected examples of school reform as a place of “new education” and analyses their architecture with regard to the educational concept, the problem of education of the “new man” within the framework of life reform and with regard to the architectural conception and arrangement of the space intended for learning. The text analyses both the “external” form of the school building and the “internal” architecture of the educational thinking of the main protagonists of both school reform examples – Eduard Štorch and Karl Metzner. The analysis of the examples of school reform is carried out in the socio-political context of Czechoslovakia in the interwar period and in the context of the efforts to reform the school architecture at the beginning of the 20th century and in the interwar period in Central Europe.